Serum vitamin D levels can be predictive of psoriasis flares up after COVID-19 vaccination: a retrospective case control study - Karampinis, Emmanouil; Goudouras, George; Ntavari, Niki; Bogdanos, Dimitrios Petrou; Roussaki-Schulze, Angeliki-Victoria; Zafiriou, Efterpi (Frontiers in Medicine, 2023)
Introduction Many patients with chronic inflammatory dermatosis such as psoriasis usually ask about the safety of COVID-19 vaccination and if it would affect the course of their disease. Indeed, many case reports, case series and clinical studies, reporting psoriasis exacerbation following vaccination against COVID-19, were published during the pandemic. Also, many questions arise regarding the existence of exacerbating factors of these flare ups, including environmental triggers such as the insufficiency of vitamin D levels. Methods This is a retrospective study that measures alterations in psoriasis activity and severity index (PASI) not exceeding 2 weeks after the first and second dose of COVID-19 vaccinations in the reported cases and assesses whether such changes have any association with patients’ vitamin D levels. We retrospectively reviewed the case records of all patients with a documented flare up after COVID-19 vaccination in our department as well as those who did not, during a year. Results Among them, we found 40 psoriasis patients that had reported vitamin D levels in the form of 25-hydroxy-vitamin D within 3 weeks after vaccination, including 23 with exacerbation and 17 without exacerbation. Performing χ2 and t-test controls for psoriasis patients with and without flare-ups, a statistically significant dependence emerged in the seasons of summer [χ2(1) = 5.507, p = 0.019], spring [χ2(1) = 11.429, p = 0.001] and in the categories of vitamin D [χ2(2) = 7.932, p = 0.019], while the mean value of vitamin D for psoriasis patients who did not have exacerbation (31.14 ± 6.67 ng/mL) is statistically higher [t(38) = 3.655, p = 0.001] than the corresponding value of psoriasis patients who had an exacerbation (23.43 ± 6.49 ng/mL). Discussion This study indicates that psoriasis patients with insufficient (21–29 ng/mL) or inadequate (<20 ng/mL) levels of vitamin D are more prone to postvaccination aggravation of the disease while vaccination in summer, a period with the most extent photo-exposition, can be a protective factor.